Landslide Hazard Mapping of Bagh District in Azad Kashmir: Landslide Hazard Mapping of Bagh District in Azad Kashmir - Sadaf Javed (International Journal of Economic and Environmental Geology, 2017)
Landslide is a process which comprises creep movement, flow movement, rockfalls, snow avalanche and soil flow on a slope. Human beings in hilly regions face catastrophe in the form of land sliding specifically during rain time period. This paper will inspect the study of landslide hazard areas detection from NASA’s Shuttle Radar Topography Mission (SRTM)’s Digital Elevation Model and moderate resolution Landsat-8 imagery over the district of Bagh in Azad Kashmir by applying hazard evaluation technique of average weighted overlay method with 6 factors in GIS environment. The outcome of this calculation is an area in the form of hazardous zones in eastern, north-eastern and south eastern of Bagh district in AJK. Landsat-8 imagery is considered effective for observing topographies over a large area while SRTM DEM (1arc second) with large global coverage provides elevation data with 30-meter resolution. GIS technique like assigning weights (weighted overlay method) on different parameters of the landslide can be helpful to policy makers and disaster management departments to overwhelm the serious situation during the hazard. Keywords: Landslide, SRTM, DEM, landsat-8, remote sensing, GIS.